Loan pricing in internal capital markets and the impact of the two-tier system: Finance groups in Germany - Ulrike Busch; Nuri Khayal; Melanie Klein (Deutsche Bundesbank, 2022)
This paper sheds light on the functioning of internal capital markets by analysing money market transactions within the German cooperatives and savings banks finance groups. Using a unique dataset, the money market statistical reporting, this is the first paper to explicitly analyze the determinants of loan rates and volumes in internal capital markets. We find that the functioning of internal capital markets diverges substantially from the non-group interbank money market. Head institutes lend larger amounts at lower spreads to their affiliated banks than to banks outside their internal capital markets. Our findings also suggests that relationship lending is associated with lower spreads in the unsecured market in general but it plays only a minor role in internal capital markets. This finding indicates that counterparty credit risk and information asymmetries are less relevant within internal capital markets. We find an almost full immediate pass-through of the reduction of the deposit facility rate in 2019 to internal capital markets, but not to the rest of the interbank money market. The introduction of the two-tier system led to a slight transitory increase in rates and to a persistent increase in loan volumes within internal capital markets but not in the rest of the interbank money market.
Keywords: E44; E43; 330; internal capital markets; monetary policy; interbank money market; relationship lending